فاعليّة برنامج قائم على استراتيجيّة لعب الدّور في تنمية بعض المفاهيم العلمية لدى طفل الرّوضة. (دراسة شبه تجريبيّة في مدينة اللاذقيّة على أطفال الرّوضة لعمر5-6 سنوات) - جناد روعة; أحمد مطيعة; علي مرفت (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Current research aimes defines the effectiveness of the role playing strategy to developing some of the scientific concepts for children who are between 5 to 6 years old Compared to the usual way. To achieve this aim the researcher experimented with this strategy by preparing a set of activities designed according to this strategy. She also prepared a pre-post test to measure some scientific concepts in kindergarten children Was distributed to a sample of 32 children. The researcher adopted the semi-empirical approach, After the completion of the application and data collection on the pre-post- photometric test, analyzed and analyzed statistically, the results showed the following: 1- There are differences of statistical significance between the average grades of children of the experimental and control groups In the post-application to test the scientific concepts, for the experimental group. 2-There are no statistically significant differences between the average scores of male and average scores of female children in the experimental group In the post-application to test the scientific concepts. The research proposed to employ the discussion strategy as an educational learning strategy in kindergartens in order to provide the child with many different skills, experiences and concepts, especially scientific concepts. هدف البحث الحالي تعرّف فاعليّة استراتيجيّة لعب الدّور في تنمية بعض المفاهيم العلميّة لدى طفل الرّوضة لعمر(5-6) سنوات مقارنة بالطّريقة المعتادة. ولتحقيق هذا الهدف قامت الباحثة بتطبيق هذه الاستراتيجيّة من خلال إعداد مجموعة من الأنشطة المصمّمة وفق لهذه الاستراتيجيّة، كما قامت بإعداد اختبار قبلي- بعدي مصوّر لقياس بعض المفاهيم العلميّة لدى أطفال الرّوضة، تمّ توزيعه على عيّنة مؤلّفة من(32) طفلاً وطفلة. اعتمدت الباحثة المنهج التّجريبي، وبعد الانتهاء من التطبيق وجمع البيانات المتعلّقة بالاختبار القبلي – البعدي المصوّر، حلّلت وعولجت إحصائيّاً، وقد أظهرت النتائج ما يلي: 1- وجود فروق ذات دلالة إحصائية بين متوسطي درجات أطفال المجموعتين التجريبيّة والضّابطة في التطبيق البعدي لاختبار المفاهيم العلمية ولصالح المجموعة التجريبيّة. 2- عدم وجود فروق ذات دلالة إحصائية بين متوسط درجات أطفال الذّكور ومتوسط درجات الإناث في المجموعة التجريبيّة في التطبيق البعدي لاختبار المفاهيم العلمية. وقدّم البحث في النهاية جملة من المقترحات كان أهمّها العمل على توظيف استراتيجيّة لعب الدّور بوصفها استراتيجيّة تعليميّة- تعلّميّة في رياض الأطفال في تنمية العديد من المهارات والخبرات والمفاهيم المتنوّعة ولا سيما المفاهيم العلميّة.